Adenocarcinoma of the Cervix Uteri and Endometrium Combined With the Kartagener Syndrome on FDG PET/CT. (November 2015) - Zhang, Yin; Chen, Yue; Huang, Zhanwen; Zhou, Fan
<x xml:space="preserve">Abstract</x> Abstract A 45-year-old woman with pathologically confirmed adenocarcinoma of the cervix uteri and endometrium underwent FDG PET/CT for staging. No metastasis was found. However, the images revealed bronchiectasis, sinusitis, and situs inversus totalis, which are the triad of Kartagener syndrome.